Fluorodeoxyglucose‐Positron Emission Tomography Predicts Bone Marrow Involvement in the Staging of Follicular Lymphoma. (28th April 2020) - St‐Pierre, Frédérique; Broski, Stephen M.; LaPlant, Betsy R.; Maurer, Matthew J.; Ristow, Kay; Thanarajasingam, Gita; Macon, William R.; Habermann, Thomas M.; Witzig, Thomas E.
Abstract: Background: Standard bone marrow biopsy (BMB) and bone involvement with follicular lymphoma (FL) on positron emission tomography (PET)/computed tomography (CT) both predict early clinical failure in FL. The key clinical question is whether PET/CT findings can obviate the need for BMB. The goal of this study was to determine the value of PET/CT in determining bone involvement in FL, using posterior iliac crest BMB as the gold standard. Materials and Methods: A total of 548 patients with newly diagnosed grade 1–3A FL were included. The presence, pattern, and location of bone involvement, spleen involvement, and standardized uptake values (SUVs) in the L3 vertebral body were recorded for all patients and compared with the BMB report. Results: Excluding patients with focal bone lesions on PET/CT, the sensitivity and specificity of PET/CT in detecting bone or marrow involvement, compared with BMB, were 53% and 88%, respectively. The sensitivity and specificity of spleen involvement on PET/CT in predicting a positive BMB were 55% and 86%, respectively. An L3 SUVmax of less than 2.0 resulted in a negative predictive value (NPV) of 96% for marrow involvement on BMB; an L3 SUVmean below 1.4 resulted in an NPV of 100%. Conclusion: In newly diagnosed FL, PET/CT‐detected bone and splenic involvement is highly specific for a positive BMB, and very low SUV values (<2.0 SUVmax and < 1.4 SUVmean ) in the lumbar spine have a high NPV for a negative BMB. Routine BMB may be obviated in these patients. BMB remains necessary to definitively exclude bone marrow involvement in a large majority of patients with a negative PET. Implications for Practice: Predicting early clinical failure in follicular lymphoma (FL) is important but difficult. Bone marrow involvement by FL is associated with early clinical failure, and determining this involvement is a key component of the initial staging. This study highlights that in certain patients, positron emission tomography/computed tomography is sufficient in determining bone or marrow involvement, without the need for a confirmatory bone marrow biopsy (BMB). An algorithm is provided based on these findings to help clinicians determine which patients would benefit from BMB and when it can be avoided. Abstract : To determine the value of PET/CT scans to confirm bone involvement in follicular lymphoma, this study compared different patterns of osseous FDG uptake detected by PET/CT with results of a standard posterior iliac crest bone marrow biopsy.